2018
DOI: 10.3389/fphys.2018.00343
|View full text |Cite
|
Sign up to set email alerts
|

Tangshen Formula Attenuates Diabetic Nephropathy by Promoting ABCA1-Mediated Renal Cholesterol Efflux in db/db Mice

Abstract: The commonly prescribed Tangshen Formula (TSF) is a traditional Chinese formulation that has been shown to reduce plasma lipid metabolism and proteinuria and improve the estimated glomerular filtration rate (eGFR) in patients with diabetic kidney disease. This study investigated the underlying mechanism whereby TSF regulates renal lipid accumulation and ameliorates diabetic renal injuries in spontaneous diabetic db/db mice and in vitro in sodium palmitate (PA)-stimulated and Abca1-SiRNA-transfected mouse tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The typical pathologic damage changes in db/db mice, including glomerular hypertrophy, mesangial expansion, thickened GBM, and abnormal deposition of fibronectin, collagen type IV, and collagen type I, were relieved by TSF or irbesartan treatment (Figures 1(e) , 1(f) , and S2 ). Therefore, TSF could effectively alleviate proteinuria and renal injury in db/db mice, which is consistent with our previously reported results [ 29 , 40 ].…”
Section: Resultssupporting
confidence: 93%
“…The typical pathologic damage changes in db/db mice, including glomerular hypertrophy, mesangial expansion, thickened GBM, and abnormal deposition of fibronectin, collagen type IV, and collagen type I, were relieved by TSF or irbesartan treatment (Figures 1(e) , 1(f) , and S2 ). Therefore, TSF could effectively alleviate proteinuria and renal injury in db/db mice, which is consistent with our previously reported results [ 29 , 40 ].…”
Section: Resultssupporting
confidence: 93%
“…The anti-lipotoxic effect of curcumin, berberine, oligonol-derived lychee fruit, and oryzanol-derived rice bran oil has also been demonstrated due to their capacity to reduce inflammatory, oxidative stress, and mitochondrial dysfunction markers in diabetic murine models [201][202][203][204][205]. Tangshen formula, a traditional Chinese formulation, was able to alleviate abnormal renal lipid accumulation and kidney damage in db/db mice by promoting ABCA1-mediated efflux cholesterol [206]. Thymol, a monoterpene phenolic compound found mainly in oil of thyme (an herb known as Thymus vulgaris) and Omacor (n-3 polyunsaturated fatty acids), decreased renal lipid accumulation through the modulation of SREBP-1-mediated lipogenic pathway [207,208].…”
Section: Polyphenols Flavonoids and Nutraceuticalsmentioning
confidence: 99%
“…In our preliminary multicenter, randomized, double-blind, and placebo-controlled trial, TSF significantly reduced proteinuria, improved the estimated glomerular filtration rate (eGFR) among patients with DKD, and exhibited a beneficial effect in improving plasma lipid metabolism (Yu et al, 2011; Li et al, 2015). Additional studies from our group also found that TSF not only exerted a renal protective effect in decreasing urinary albumin excretion rate and glomerulosclerosis but also improved lipid metabolism in spontaneous DKD rodents, including Otsuka Long-Evans Tokushima Fatty rats and db/db mice (Zhang et al, 2011; Kong et al, 2016; Liu et al, 2018). However, little is known about the effect and potential mechanism of TSF on hepatic steatosis.…”
Section: Introductionmentioning
confidence: 72%